The humanitarian role of the Algerian Red Crescent during the libération revolution - sellami, hadjira; yaiche, mohamed (Journal of Social Sciences and Humanities, 2021)
Despite the many fronts of the fighting and the struggle waged by the Algerian revolution in all segments of its society, it did not lose sight of any opportunity to help the Algerians. The society, especially the refugees who chose Tunisia and Morocco as their refuge, and with the intensification of the war and the development of the infernal methods of France began to harvest green and hard without taking into account the human side of the Algerian people, adopting a method of intimidation and intimidation in order to make Algeria a French land,It also displaced the inhabitants of the eastern and western borders in order to isolate the revolution from the people and eliminate it in the cradle, after it got rid of a large part of its population and aimed them into the unknown. Many of the humanitarian agencies and organizations, most notably the Algerian Red Crescent, were to provide assistance to all the Algerian people.